Flexible, customisable and good looking: multiple uses for Wordpress MU in two Australian Libraries - Greenhill, Kathryn (Australian Library and Information Association, 2011)
Wordpress MU (Multiuser) is Open Source software that at its simplest is a blogging platform that allows a number of users to run several different blogs on the one database installation. WordpressMU is also sophisticated and customisable enough to be used as a fully fledged Content Management System or to create an entire social networking platform. This paper describes two case studies of Wordpress MU used to provide very different solutions in two different libraries. Neither library used the platform to create blogs as the layperson understands them - reflective online journals. The paper outlines how and why the platform was chosen, decisions about hosting and the stakeholder negotiations required to have the solution accepted within the organisations. It describes the necessary customisation decisions and how these diverged with the different purposes. The first case study involves a scientific research library service with technologically sophisticated, widely dispersed users who required an up-to-date current awareness service from multiple contributors. The second case-study involves a public library with a very simplistic and rigid website that was hosted by a design company and a need to formalise communication procedures before the move to a new library building made it much harder for staff to share information. The paper also describes how the development of the new services were used as an opportunity to identify staff training requirements and introduce the potential of tools such as RSS, Yahoo Pipes, Netvibes, Twitter and Flickr to enhance the information in the Wordpress MU installations.